2004
DOI: 10.1103/physreve.69.051702
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic-nematic phase transition in suspensions of filamentous virus and the neutral polymer Dextran

Abstract: We present an experimental study of the isotropic-nematic phase transition in an aqueous mixture of charged semi-flexible rods (fd virus) and neutral polymer (Dextran). A complete phase diagram is measured as a function of ionic strength and polymer molecular weight. At high ionic strength we find that adding polymer widens the isotropic-nematic coexistence region with polymers preferentially partitioning into the isotropic phase, while at low ionic strength the added polymer has no effect on the phase transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 46 publications
13
144
2
Order By: Relevance
“…Under high-salt conditions, hard-core repulsive interactions dominate the behavior of fd/polymer mixtures, and consequently all phase transitions in this system are entropically driven (8). Similar mixtures have been used to explore the influence of attractive interactions on the isotropic-nematic phase transition and kinetics of various liquid crystalline phase transitions (9)(10)(11). In these studies, the qualitative observation of 2D membrane-like structures was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Under high-salt conditions, hard-core repulsive interactions dominate the behavior of fd/polymer mixtures, and consequently all phase transitions in this system are entropically driven (8). Similar mixtures have been used to explore the influence of attractive interactions on the isotropic-nematic phase transition and kinetics of various liquid crystalline phase transitions (9)(10)(11). In these studies, the qualitative observation of 2D membrane-like structures was reported.…”
Section: Resultsmentioning
confidence: 99%
“…They found an increase of the entropy of the polymer spheres when the hard particles were moved together, leading to an effective attraction between the particles. Depletion forces have been observed and analyzed theoretically in a variety of systems, including mixtures of large and small colloidal particles, both with spheres and rods, mixtures of colloidal particles and polymers, and mixtures of proteins and polymers, inducing either or both particle aggregation and phase separation (21,24). Depletion forces also are credited as being responsible for the formation of protein crystals in mixtures of proteins and polymers such as PEG (17).…”
Section: Entropy and Energy Combine To Drive The Ndna Phase Separationmentioning
confidence: 99%
“…We use the fd -virus, which is an excellent model liquid crystal system for both static and dynamic behaviour [13][14][15][16]. The virus' contour length and diameter are 0.88 µm and 6.6 nm, respectively.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…We introduce a new method for estimating elastic constants suitable to colloidal and biological systems, as an alternative to previous methods using magnetic fields [11] or light scattering [12]. Specifically, we determine the transition from a splay to a bend director field, with increasing wedge angle.We use the fd -virus, which is an excellent model liquid crystal system for both static and dynamic behaviour [13][14][15][16]. The virus' contour length and diameter are 0.88 µm and 6.6 nm, respectively.…”
mentioning
confidence: 99%